1994
DOI: 10.1089/dna.1994.13.395
|View full text |Cite
|
Sign up to set email alerts
|

Gene Organization of the Mouse Pro-Hormone and Pro-Protein Convertase PC1

Abstract: Using a probe consisting of either the 5' end sequence or the full-length cDNA sequence of the mouse prohormone convertase PC1 (mPC1), we isolated from a lambda EMBL3 mouse genomic library two clones that coded for the 5' and 3' ends of the mPC1 gene. The complete gene organization was obtained by combining the results of the sequence of these clones and those of the characterization of polymerase chain reaction-amplified genomic segments. The single-copy mPC1 gene, confirmed by Southern analysis, spans at lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
21
0

Year Published

1996
1996
2012
2012

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(22 citation statements)
references
References 53 publications
(107 reference statements)
1
21
0
Order By: Relevance
“…The targeting strategy we used (see Text, which is published as supporting information on the PNAS web site, www.pnas.org) resulted in the deletion of exon 1 and several putative upstream transcriptional control elements (CRE, ICS, GHF-1, AP-1, and Sp1) from the PC1͞3 (PCSK1) gene (26). Homozygous PC1͞3-null offspring were obtained by mating heterozygous male and female siblings (Fig.…”
Section: Pc1͞3 Expression Is Abolished In Homozygous-null Micementioning
confidence: 99%
“…The targeting strategy we used (see Text, which is published as supporting information on the PNAS web site, www.pnas.org) resulted in the deletion of exon 1 and several putative upstream transcriptional control elements (CRE, ICS, GHF-1, AP-1, and Sp1) from the PC1͞3 (PCSK1) gene (26). Homozygous PC1͞3-null offspring were obtained by mating heterozygous male and female siblings (Fig.…”
Section: Pc1͞3 Expression Is Abolished In Homozygous-null Micementioning
confidence: 99%
“…All PCR primers were designed using the GCG "primer" program (see Table III). The forward and the reverse primer sequences were selected from exonic sequences separated by conserved splice sites in PC1, PC2, and furin (45).…”
Section: Endoproteolytic Cleavage Of Gp160 and Inhibitor Assays-[mentioning
confidence: 99%
“…In β cells, insulin decreases intracellular cAMP (53) and glucose increases cAMP (54,55), whereas in α cells, the insulin and glucose regulation of cAMP has not been studied. Both the low insulin and high glucose in the STZ-treated islet would be expected to increase PC1 and PC2 promoter activity, as the promoter of these 2 genes has cAMP-response elements (CREs) (56)(57)(58)(59). In other experiments, we found that glucose stimulates PC1 and PC2 promoter activity in the insulin-secreting RIN 1046-38 cell line and the glucagon-secreting αTC1-6 cell line, and that for PC1, this stimulation required intact CREs on the PC1 promoter (Q.-L. Li et al, in preparation).…”
mentioning
confidence: 99%